Funcionarios Unidad de Seguridad.
Once personas entre ellas de izquierda a derecha Walter Aguilar, Trino Montero, Rafael Cerdas, Roberto Chacón, Juan Diego Granados, Juan Carlos Ulloa, abajo: Mario Sibaja, Luis Moncada, Arturo Céspedes, Esteban Montero